Natural Products for Antithrombosis. (17th May 2015) - Chen, Cen; Yang, Feng-Qing; Zhang, Qian; Wang, Feng-Qin; Hu, Yuan-Jia; Xia, Zhi-Ning
Abstract : Thrombosis is considered to be closely related to several diseases such as atherosclerosis, ischemic heart disease and stroke, as well as rheumatoid arthritis, hyperuricemia, and various inflammatory conditions. More and more studies have been focused on understanding the mechanism of molecular and cellular basis of thrombus formation as well as preventing thrombosis for the treatment of thrombotic diseases. In reality, there is considerable interest in the role of natural products and their bioactive components in the prevention and treatment of thrombosis related disorders. This paper briefly describes the mechanisms of thrombus formation on three aspects, including coagulation system, platelet activation, and aggregation, and change of blood flow conditions. Furthermore, the natural products for antithrombosis by anticoagulation, antiplatelet aggregation, and fibrinolysis were summarized, respectively.